Effect of Changes in Dietary Net Energy Concentration on Growth Performance, Fat Deposition, Skatole Production, and Intestinal Morphology in Immunocastrated Male Pigs - Batorek-Lukač, Nina; Čandek-Potokar, Marjeta; Škrlep, Martin; Kubale, Valentina; Labussière, Etienne (Frontiers in Veterinary Science, 2021)
Nutritional requirements of heavy immunocastrated pigs (IM) and therefore appropriate feeding strategies have not yet been determined. Thus, the effects of changes in dietary net energy (NE) content were studied in 41 IM, fed ad libitum diets with low, medium, or high NE content (LNE, MNE, and HNE diets; with 8.5, 9.3, and 10.0 MJ NE/kg), from 84 days of age until slaughter at an average age of 172 days and 122.5 kg average body weight. In the period from 143 to 170 days of age, there was a tendency for a greater NE intake (p = 0.08) in pigs fed the HNE diet along with greater (p < 0.01) backfat gain. Dietary treatment affected carcass composition as lower backfat thickness (p = 0.01) and lower area of fat over the longissimus muscle (p = 0.05) were observed in LNE and MNE pigs. In addition, greater lean meat content (p = 0.04) was observed in LNE pigs. Reducing the NE of the diet by replacement of cereals and soybean meal with high fiber ingredients resulted in lower indole production in the ascending colon (p < 0.01), and greater skatole production (p < 0.01) in the cecum. Greater villi area, width, height and perimeter, crypt depth, and thickness of the intestinal mucosa in the jejunum, ileum, ascending colon, and descending colon were found for the LNE group (p < 0.01) than for the HNE group, while the MNE group was intermediate. Cell proliferation was not affected by dietary treatment (p > 0.05). The present results show that a reduction in dietary NE concentration lowers lipid deposition, without affecting performance or energy efficiency in IM pigs. This technique provides an advantage in terms of improved leanness, without affecting growth rate in IM after immunization, which is particularly important when the backfat thickness is a determinant of carcass value and IM are fattened to higher weights (e.g. in heavy pig production) or when a longer delay between immunization and slaughter is practiced.